Fantastic Mr. Fox - Dahl, Roald (London : Puffin Books, 2013)
A storybook version of the 2009 film adaptation of Roald Dahl's "Fantastic Mr. Fox," the story of a fox who comes up with a way to outfox the trio of gross and greedy farmers that has him and his family trapped in their home.
3.0
K-3.
K-3
Keywords: Farmers -- Juvenile fiction; Foxes -- Juvenile fiction; Farmers -- Fiction; Foxes -- Fiction; Farmers -- Fiction; Foxes -- Fiction; Movie novels